2021
DOI: 10.1111/cns.13632
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant multimodal brain networks in patients with anti‐NMDA receptor encephalitis

Abstract: Aims To explore large‐scale brain network alterations and examine their clinical and neuropsychological relevance in patients with anti‐N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis. Methods Twenty‐four patients with anti‐NMDAR encephalitis and 26 matched healthy controls (HCs) were enrolled in our study. Based on the multimodal MRI dataset, individual morphological, structural, and functional brain networks were constructed and compared between the two groups at multiple levels. The associations with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Adult AE studies have found associations between fMRI connectivity in regionally defined networks with working memory and processing speed 18, 91 . Previous fMRI studies in NMDARE observed a higher connectivity to neighbouring nodes in the right lateral orbital gyrus compared to controls 66 , and lower clustering coefficient and local efficiency in the left insula 65 , which suggests differing local areas within a network could be identified in future studies. The present study lacked statistical power to investigate specific regions of interest and was focused on global and average measures of network efficiency.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Adult AE studies have found associations between fMRI connectivity in regionally defined networks with working memory and processing speed 18, 91 . Previous fMRI studies in NMDARE observed a higher connectivity to neighbouring nodes in the right lateral orbital gyrus compared to controls 66 , and lower clustering coefficient and local efficiency in the left insula 65 , which suggests differing local areas within a network could be identified in future studies. The present study lacked statistical power to investigate specific regions of interest and was focused on global and average measures of network efficiency.…”
Section: Discussionmentioning
confidence: 88%
“…Measures of efficiency and modularity, that reflect how well brain networks integrate and segregate distinct modules to efficiently transmit neuronal information, were chosen. These specific measures were investigated as they were applied in previous AE fMRI research 65, 66 .…”
Section: Methodsmentioning
confidence: 99%
“…However, some of these studies focused on the superficial white matter areas rather than the whole-brain including white-gray matter and deep gray matter areas of recovered and partially recovered patients (Phillips et al, 2018), while others used Tract-Based Spatial Statistic (TBSS) analysis methods that were inconsistent with ours (Finke et al, 2013;Yang et al, 2022). Recently, Wang et al applied multimodal brain network analysis to show that changes in structural networks were mainly in fiber number and fiber length, and very few significant changes in FA in anti-NMDAR encephalitis (Wang et al, 2021), which is consistent with our findings. While in our research, we didn't found changes of DTI parameters in white matter.…”
Section: White Matter Microstructural Changesmentioning
confidence: 99%
“…The pathological changes might involve NMDAR-Ab, which changes intrinsic cortical connections and neuronal population dynamics (Rosch et al, 2018;Dalmau et al, 2019). To the best of our knowledge, most studies in the literature have focused on changes in brain networks using magnetic resonance imaging (MRI) and electroencephalography (EEG) in patients with encephalitis (Peer et al, 2017;Xu et al, 2017;Heine et al, 2018;Symmonds et al, 2018;Bauer et al, 2020;Li et al, 2021;Wang et al, 2021), while the use of 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) has not been reported before, which is earlier for recognition and more sensitive than MRI (Novy et al, 2016;Yuan et al, 2016;Wei et al, 2020;Seniaray et al, 2021). Metabolic brain network analysis based on graph theory has proved useful in analyzing brain activity changes and is widely used in neuropsychological imaging (Huang et al, 2020;Rajagopalan and Pioro, 2020).…”
Section: Introductionmentioning
confidence: 99%